2016
DOI: 10.5433/1679-0359.2016v37n6p3881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the interaction between fungicide application time and rainfall simulation interval on Asian Soybean Rust control effectiveness

Abstract: Environmental factors affect the performance of fungicides in soybean (Glycine max (L.) Merr.). They also influence the residual activity of the products applied to the leaves. The objective of this study was to assess the control effectiveness of the interaction between fungicide application and rainfall simulation on Asian Soybean Rust (ASR). Two experiments were conducted, one in the greenhouse, in a completely randomized design, and the other in the field, in a randomized block design. Both the experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In soybeans, the rainfall simulation, even 120 min after fungicide application, decreased the Asian soybean rust control effectiveness (Stefanello et al 2016). It is important to highlight that different factors may impact the effect of products employed in disease control, including plant genotype, product, adjuvant, leaf age, drop size and time of application (Stefanello et al 2016). The results indicate that Cu afforded a better tenacity to phosphite than K. Therefore, less removal of Cu phosphite deposits on coffee leaves should be expected due to rainfall under field conditions.…”
Section: Phosphites and Coffee Leaf Rust Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In soybeans, the rainfall simulation, even 120 min after fungicide application, decreased the Asian soybean rust control effectiveness (Stefanello et al 2016). It is important to highlight that different factors may impact the effect of products employed in disease control, including plant genotype, product, adjuvant, leaf age, drop size and time of application (Stefanello et al 2016). The results indicate that Cu afforded a better tenacity to phosphite than K. Therefore, less removal of Cu phosphite deposits on coffee leaves should be expected due to rainfall under field conditions.…”
Section: Phosphites and Coffee Leaf Rust Controlmentioning
confidence: 99%
“…Despite the absence of literature dealing with the effect of washing on phosphite's performance, the efficiency of pesticides is known to be affected by leaf washing. In soybeans, the rainfall simulation, even 120 min after fungicide application, decreased the Asian soybean rust control effectiveness (Stefanello et al 2016). It is important to highlight that different factors may impact the effect of products employed in disease control, including plant genotype, product, adjuvant, leaf age, drop size and time of application (Stefanello et al 2016).…”
Section: Phosphites and Coffee Leaf Rust Controlmentioning
confidence: 99%
“…Several studies reported that rainfall itself is considered an epidemic triggering factor for SBR occurrence (Del Ponte et al, 2006;Megeto et al, 2014) since it enhances periods with free water over the plant surfaces. Once rainfall is strongly related to within-canopy spore dispersal, such a variable has a remarkable influence on the performance of fungicide sprays applied for SBR control (Stefanello et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…Besides air temperature and LWD, rainfall can also affect SBR occurrence. Rainfall regime is considered to be an epidemic triggering factor of SBR, by creating a favorable environment for the pathogen (Del Ponte et al, 2006;Megeto et al, 2014) and unfavorable for fungicide spray application in order to control the SBR (Stefanello et al, 2016). Influence of rainfall on SBR progress was observed in Brazil, where areas with rainfall between 250 and 450 mm showed final disease severity over 70%; whereas areas with rainfall lower than 125 mm presented severity below 30% (Del Ponte et al, 2006).…”
mentioning
confidence: 99%
“…Studies have shown that the adverse effect of rain is directly related to the interval between pesticide application and its occurrence (Stefanello et al, 2016). Debortoli (2008) showed that simulated rain affected the control of Asian soybean rust negatively, especially when no adjuvant was used mixed with the fungicide.…”
Section: Introductionmentioning
confidence: 99%